Design of mechatronic simulators to improve the quality of students learning outcomes in mechatronics subject - Kustija, J; Hasbullah, H; Somantri, Y (Journal of physics. Conference series, 2019)
Today condition in learning mechatronics subject, especially at Universitas Pendidikan Indonesia Departemen Pendidikan Teknik Elektro still uses learning object and software simulations. This still has not maximized student's competency in the mechatronics subject, which is required to be skilled in real engineering that will be applied both in the industry and in educational institutions. According to the Universitas Pendidikan Indonesia research master plan which establish its vision to be a Pioneer and Superior University in the field of education, then research on learning innovation is directed to aspects of learning, that is research on learning models, learning media, organizing learning implementation plans, organizing learning materials, and evaluation systems. Learning innovation products generated from this research are expected to be a reference and become the main pillar for all academic units in the UPI environment in implementing learning. Based on the above idea, the researcher proposes to develop a learning media that is corresponding with the requirement of mechatronics subject in the competency based on applicative design mechatronics simulator. The method used in this research is quantitative method with research and development approach. The excellent research of the college with the title "Design Mechatronics Simulators to Improve the Quality of Student Learning On Mechatronics Subject" is a research needed to implement a design that serves as a learning media to improve learning outcomes and student's competency in mechatronics subjects.